Thirty years of the hypothesis on fluctuating stocks of pink salmon Oncorhynchus gorbuscha (Walbaum) - Sergey P. Pustovoit (Известия ТИНРО)
Hypothesis on fluctuating stocks of pink salmon was proposed 30 years ago by M.K. Glubokovsky and L.A. Zhivotovsky. Some stages of its development are analyzed in compare with traditional approach of local stocks. There is concluded that experimental verification of the basic theoretical assumptions of this hypothesis are required.